Mobile Applications for E-Scooter Navigation: A Multimedia Design Approach - Mingaile Aušrine Maželyte (2024)
This thesis explores the integration of multimedia design principles in the development of a mobile navigation application specifically tailored for e-scooter users. As e-scooters are increasingly used in cities as a flexible and environmentally friendly means of transport, there is a strong need to increase their usability and safety through innovative navigation solutions. This study employs a comprehensive methodology combining focus groups, expert interviews, and prototyping to address this need. The research was initiated with focus groups to gather direct user insights on e-scooter navigation preferences and safety concerns. Following this, expert interviews were conducted with professionals in micromobility and urban transport to incorporate industry-specific insights into the application's development. The insights garnered from these qualitative studies informed the design and iterative testing of a functional e-scooter navigation prototype, developed using Figma for its strong interactive capabilities. Analysis of the data from these methodologies revealed key design requirements and preferences, which were instrumental in the prototype development phase. The final prototype demonstrated a user-centered design that not only prioritizes user safety but also enhances the overall user experience through intuitive interface and practical functionality. This study not only contributes to academic knowledge in multimedia and user experience design but also provides practical implications for the development of navigation tools that can integrate seamlessly into the urban micromobility landscape. By effectively combining theoretical frameworks with empirical research, this thesis presents a detailed exploration of how multimedia design can be used to improve the safety and efficiency of e-scooter navigation systems, ultimately enabling better integration of e-scooters into the urban transportation environment.